2009
DOI: 10.5194/bg-6-3071-2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet B radiation on (not so) transparent exopolymer particles

Abstract: Abstract. Transparent exopolymer particles (TEP) are the most ubiquitous gel particles in the ocean and form abiotically from dissolved precursors. Although these particles can accumulate at the ocean surface, being thus exposed to intense sunlight, the role of solar radiation for the assembly and degradation of TEP is unknown. In this study, we experimentally determined the effects of visible and ultraviolet B (UVB) radiation on (1) TEP degradation (photolysis experiments), (2) TEP assembly from dissolved pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 39 publications
(48 reference statements)
6
58
0
Order By: Relevance
“…Wurl et al (2011) found that 10 ± 4% of the TEP in bulk seawater stuck to the inside of the inside of glass bottles. Similarly, Ortega-Retuerta et al (2009) found that 11 ± 3% of TEP model compounds (using (alginic acid and gum xanthan) stuck to the inside of borosilicate glass bottles. Wurl et al (2011) noted that TEP also sticks to the glass plates used to collect SML samples, but that the plates became "conditioned" once they have been dipped in the water a few times and did not take up any more TEP.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Wurl et al (2011) found that 10 ± 4% of the TEP in bulk seawater stuck to the inside of the inside of glass bottles. Similarly, Ortega-Retuerta et al (2009) found that 11 ± 3% of TEP model compounds (using (alginic acid and gum xanthan) stuck to the inside of borosilicate glass bottles. Wurl et al (2011) noted that TEP also sticks to the glass plates used to collect SML samples, but that the plates became "conditioned" once they have been dipped in the water a few times and did not take up any more TEP.…”
Section: Discussionmentioning
confidence: 90%
“…Work over the last 20 years has shown that TEP are ubiquitous and play an important role in particle dynamics and carbon cycling in the ocean (see reviews by Passow, 2002a;Burd and Jackson, 2009;Verdugo, 2012). Ultraviolet light enhances TEP production by microorganisms (Ortega-Retuerta et al, 2009), indicating that the high concentrations of microorganisms in the SML may be a significant source of TEP. However, the effects of ultraviolet light are complex as it also causes TEP photolysis (Ortega-Retuerta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid regression line is shown for a significant relationship considering all data for inland waters, while a dashed line is shown for nonsignificant relationship considering all data for marine waters. Data were obtained as follows: this study (Table 1) Corzo et al (2005) and Bhaskar and Bhosle (2008) The higher incident solar radiation in the Mediterranean in comparison to north temperate region could promote the release of TEP by bacteria as a solar protection screen, since TEP effectively absorb in the ultraviolet range (Ortega-Retuerta et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Sea ice algae are known to excrete high amounts of extracellular polymeric substances (EPS) that constitute a substantial fraction of the DOC pool in sea ice [12,13]. EPS are produced as a normal cell function and used for motility, aggregation, desiccation, cryoprotection and protection against ultraviolet radiation [13][14][15]. The release of DOC is an important nutrient source for heterotrophic bacteria and may therefore affect microbial ecology and biogeochemistry [16].…”
Section: Introductionmentioning
confidence: 99%